Description of anti-diabetic drug utilization pre- and post-formulary restriction of sitagliptin: findings from a national health plan. (3rd August 2015) - Huang, Xingyue; Liu, Zhiwen; Shankar, Ravi R.; Rajpathak, Swapnil
Abstract: Objective: Multi-tiered formularies are commonly used for controlling costs of prescription medications. Focused on type 2 diabetes mellitus (T2DM), this database study assessed drug utilization before and after a formulary restriction (2nd–3rd tier), and compared demographic and clinical characteristics of patients affected vs not by the restriction. Methods: Formulary restriction of sitagliptin (SITA) occurred July 1, 2012. The 'pre-period' was defined from January 1–June 30, 2012, the 'grace period' from July 1–September 30, 2012, and the 'post-period' from October 1, 2012–March 31, 2013. Patients from the OptumInsight database were included if diagnosed with T2DM, ≥18 years, had continuous enrollment, and had ≥2 prescriptions of SITA in the pre-period. Those who died or were aged ≥65 years in the post-period were excluded. Patients were grouped into SITA continuer and discontinuer cohorts based on SITA use in the post-period. Descriptive analyses assessed baseline patient characteristics and anti-hyperglycemic drug utilization in the pre- and post-periods. Results: In total, 23, 477 patients met inclusion criteria. In the post-period, 36.1% ( n = 8480) of patients discontinued SITA. Among SITA discontinuers, 44.1% switched to a preferred DPP-4 inhibitor, 9.2% switched to glucagon-like peptides-1 (GLP-1) or insulin, and 2.4% switched to metformin or sulfonylurea. Of the SITA discontinuers, 21.6% dropped SITA without replacement and 8.4% discontinued all diabetes medications. In the post-period, a greater proportion of SITA discontinuers used GLP-1 (12.6% vs 5.8%) and insulin (29.1% vs 20.9%) than continuers, or had some change in anti-hyperglycemic treatment (67.5% vs 22.1%). Baseline demographic and clinical characteristics were similar between SITA continuers and discontinuers, indicating a lack of an association with SITA discontinuation. Limitations: This descriptive study used a non-controlled observational approach. Conclusions: Following formulary change, 1/3 of patients discontinued SITA and 30% of discontinuers received less intensive anti-hyperglycemic treatment in the post-restriction period. Meanwhile, 44% of discontinuers switched to a new preferred DPP-4 inhibitor.